38. FREQUENCY OF OSTEOPOROSIS IN PATIENTS WITH CUSHING’S SYNDROME DUE TO GLUCOCORTICOID USE AT THE DEPARTMENT OF ENDOCRINOLOGY – NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To survey the status of osteoporosis and density in patients using long-term glucocorticoids. Methods: The study of cross-sectional descriptive, all 60 patients had a history or were currently taking glucocorticoid drugs. Research period from February 2023 - June 2023 at the Department of Endocrinology, Nghe An General Friendship Hospital.Results: Mean age 65.4 ± 9.3 years; The ratio of women is 58.3% and men is 41.7%. The average duration of glucocorticoid use was 42.4 ± 28.5 months. The average values of bone density BMD CSTL and CXD are 0.7 ± 0.1g/cm2 and 0.6 ± 0.1 g/cm2 , respectively. The average values of T-score CSTL and CXD are -2.4 ± 1.0 and -2.1 ± 0.7, respectively. Osteoporosis rate 60%. Patients who used GC drugs for 2 years or more were 5 times more likely to have osteoporosis complications than those who used GC for less than 2 years (OR = 5.0; 95%CI: 1.5 - 16.4; p = 0.006 ). There is a negative linear correlation between CSTL BMD and duration of glucocorticoid use with a strong correlation (r = - 0.765, p < 0.001). The group of patients using glucocorticoids for one year or more had an average CSTL BMD of 0.7 ± 0.01, lower than those using less than one year (0.9 ± 0.1) with p < 0.05. The group of patients using glucocorticoids for one year or more had an average BMD of 0.6 ± 0.01, lower than those using less than one year (0.7 ± 0.1) with p < 0.05.Conclusion: Long-term use of glucocorticoids affects bone density and increases the risk of osteoporosis.
Keywords: Cushing’s syndrome, Osteoporosis, glucocorticoids